Pre-clinical model of severe glutathione peroxidase-3 deficiency and chronic kidney disease results in coronary artery thrombosis and depressed left ventricular function. Issue 6 (13th December 2017) - Pang, Paul; Abbott, Molly; Abdi, Malyun; Fucci, Quynh-Anh; Chauhan, Nikita; Mistri, Murti; Proctor, Brandon; Chin, Matthew; Wang, Bin; Yin, Wenqing; Lu, Tzong-Shi; Halim, Arvin; et al.
ABSTRACT: Background: Chronic kidney disease (CKD) patients have deficient levels of glutathione peroxidase-3 (GPx3). We hypothesized that GPx3 deficiency may lead to cardiovascular disease in the presence of chronic kidney disease due to an accumulation of reactive oxygen species and decreased microvascular perfusion of the myocardium. Methods . To isolate the exclusive effect of GPx3 deficiency in kidney disease–induced cardiac disease, we studied the GPx3 knockout mouse strain (GPx3 −/− ) in the setting of surgery-induced CKD. Results . Ribonucleic acid (RNA) microarray screening of non-stimulated GPx3 −/ − heart tissue show increased expression of genes associated with cardiomyopathy including myh7, plac9, serpine1 and cd74 compared with wild-type (WT) controls. GPx3 −/− mice underwent surgically induced renal mass reduction to generate a model of CKD. GPx3 −/−  + CKD mice underwent echocardiography 4 weeks after injury. Fractional shortening (FS) was decreased to 32.9 ± 5.8% in GPx3 −/− + CKD compared to 62.0% ± 10.3 in WT + CKD (P < 0.001). Platelet aggregates were increased in the myocardium of GPx3 −/−  + CKD. Asymmetric dimethylarginine (ADMA) levels were increased in both GPx3 −/−  + CKD and WT+ CKD. ADMA stimulated spontaneous platelet aggregation more quickly in washed platelets from GPx3 −/− . In vitro platelet aggregation was enhanced in samples from GPx3 −/−  + CKD. Platelet aggregation in GPx3 −/−  + CKD samples was mitigated after in vivo administration of ebselen, a glutathione peroxidase mimetic. FS improved in GPx3 −/−  + CKD mice after ebselen treatment. Conclusion: These results suggest GPx3 deficiency is a substantive contributing factor to the development of kidney disease–induced cardiac disease.